Barreiras socioculturais e econômicas na restauração ecológica - Marconato, Gisele Mondoni [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The success and scale broadening of ecological restoration initiatives depend on the effective engagement of rural communities. Farmers, who are the most affected stakeholders and responsible for the largest number of properties were restoration is needed, have not been engaged in this process even in the large-scale initiatives already existing in Brazil. In order to achieve this engagement, it is necessary to know the perceptions and motivations of farmers towards ecological restoration. We aimed with this study to diagnose the main barriers hinting the effective participation of farmers in ecological restoration. The study involved 82 farmers from Botucatu County, located in central-southern region of the state of São Paulo, Brazil, in which 50% are smallholders, 30% small farmers, 11% medium producers and 9% large farmers. Criteria for properties selection prioritized the ones located at the Botucatu Environmental Protection Area (APA). Semi-structured interviews were carried out, addressing issues related to the conditions of physical and biotic environment, cultural background, socioeconomic aspects and perceptions about the role of forests in the property. Among respondents, 88% own remaining forest in areas acting as spring buffers, demonstrating their interest in conserving water in their propertie. Nevertheless, only 34% of respondents expressed interest in restoring degraded areas and legal reserves where necessary. It is noticeable that most producers, regardless of the size of their properties and economic situation, are aware of the importance of forests in maintaining and protecting the water sources. However, most respondents do not show motivation towards reforestation of degraded areas and biodiversity restoration. Key-factors considered by them were the association of restoration activities only with legal obligations; the lack of recognition of the role of forests in their proper...

O sucesso e ampliação da escala das iniciativas de restauração dependem da participação e engajamento das comunidades rurais. Mesmo nas iniciativas em larga escala já existentes no Brasil, os produtores rurais, responsáveis pela maior parte das áreas que necessitam de restauração, não tem sido incluídos no processo. Para que essa participação possa ser efetivada, é necessário conhecer as percepções e motivações do agricultor sobre o tema da restauração ecológica. Tivemos com este estudo o objetivo de diagnosticar as principais barreiras que impedem a participação efetiva dos produtores rurais na restauração ecológica. O trabalho envolveu 82 produtores rurais do município de Botucatu, região centro-sul do Estado de São Paulo, Brasil, sendo 50% deles minifundiários, 30% pequenos produtores, 11% médios produtores e 9% grandes produtores rurais. A amostragem das propriedades procurou abranger aquelas localizadas dentro da APA (Área de Proteção Ambiental) de Botucatu. Entrevistas semiestruturadas foram aplicadas, abordando assuntos ligados às condições do ambiente físico e biótico, arcabouço sociocultural, aspectos socioeconômicos e percepções sobre o papel das florestas na propriedade. Dentre os entrevistados, 88% possuem remanescente florestal em áreas protetoras de água, principalmente em nascentes, demonstrando o interesse em conservar a água em suas propriedades, e apenas 34% dos entrevistados demonstraram interesse em restaurar áreas degradadas. A maioria dos produtores, independente do tamanho de suas propriedades e situação econômica, tem consciência sobre a importância das florestas na manutenção e proteção das nascentes, mas não desmonstram motivação para o reflorestamento ...
Keywords: Área de preservação permanente; Comunidades agrícolas - Entrevistas; Reflorestamento; Mata Atlântica; Area of permanent protection